Technology and the human prospect: Essays in honour of Christopher Freedom - Roy Macleod (ed.) (London, 1986)
During the last twenty years, the field of technology policy has become established y within many universities' curricula. Among the founders of this field is Christopher Freeman, R.M. Phillips Professor of Science Policy at the University of Sussex. During this time, Professor Freeman has broken new ground in the study of technology and industrial innovation, in the measurement of science and technology and in the relationship between technology and employment. In this process, Freeman has represented the problems of shaping policy to fit human aspirations, in ways which economic and social theorists have yet fully to assimilate. This book provides an opportunity to consider the 'agenda' that policy-makers and academic theorists have yet to comprehend fully.
Keywords: Technology- Social Aspects